Amperometric Determination of Nickel(II), Copper(II), Zinc(II) and Cadmium(II) using 3-Phenyl Rhodanine - Kshirsagar, Versha; Gandhi, Sandhya; Dave Gautam, Mangla (Asian Journal of Chemistry, 2010)
3-Phenyl rhodanine is employed as amperometric reagent for the trace determination of metals such as Ni(II), Cd(II), Cu(II) and Zn(II) in 30% dimethyl formamide-aqueous Britton Robinson buffer at pH 5.80, 5.68, 5.11 and 5.01 respectively with μ = 0.1 M (KCl) and fresh 0.001% gelatin. Titration potential has been selected in the limiting region of the cathodic wave of the present metals. The titrations were performed using 3-phenyl rhodanine as titrant. L-shaped curve is obtained. The statistical analysis of the observed data reveals high accuracy and precision.